Deep Futures: Transcending the Boundaries of “Money and Machines” Paradigm - Marcus Anthony (Foresight and STI Governance, 2012)
The world has been in a state of economic uncertainty since the 2008 financial crisis. Despite efforts by governments worldwide to stabilize the system and return to business as usual, the future remains unclear. Times of crisis are opportunities to introspect and to question deeply the foundations of society, culture and education. According to Einstein, “problems cannot be solved by the level of awareness that createdthem». The hegemony of a critical/rational worldview in modern society, science and education results in the shaping of an artificially narrow, «money and machines” future that diminishes universal values and deeper psycho-spiritual needs of human beings. Such a narrow focus of policy will likely aggravate social and psychological problems.